THE ALGORITHM OF DISTRIBUTING OF ELECTRICAL MOUNTING COMPLETE SETS BETWEEN A TECHNOLOGICAL TRANSPORT - Литвиненко, О.; Цивінський, К. (Science-based technologies, 2010)
The algorithm of decision of task of distributing of electrical mounting complete sets for editing of objects between a technological transport is developed. The resulted algorithm allows to minimize the term of implementation of complex electrical mounting works at presence of the limited amount of units of technological transport.